Speech as the Basic Interface for Assistive Technology - Teixeira, A.; Braga, D.; Luis Pinto Coelho; Fonseca, J.; Alvarelhão, J.; Martín, I.; Queirós, A.; Rocha, N.; undefined; Dias, J. (DSAI’09, DSAI Software Development for Enhancing Accessibility and Fighting Info-exclusion, 2009)
Speech Interfaces for Assistive Technologies are not common and are usually replaced by others. The the market they are targeting is not considered attractive and speech technologies are still not well spread. The industry still thinks they present some performance risks, especially Speech Recognition systems. As speech is the most elemental and natural way for communication, it has a strong potential for enhancing inclusion and quality of life for broader groups of users with special needs, such as people with cerebral palsy and elderly staying at their homes. This work is a position paper in which the authors argue for the need to make speech become the basic interface in assistive technologies. Among the main arguments, we can state: speech is the easiest way to interact with machines; there is a growing market for embedded speech in assistive technologies, since the number of disabled and elderly people is expanding; speech technology is already mature to be used but needs adaptation to people with special needs; there is still a lot of R&D to be done in this area, especially when thinking about the Portuguese market. The main challenges are presented, and future directions are proposed